Atg8ylation as a host-protective mechanism against Mycobacterium tuberculosis - Deretic, Vojo (Frontiers in Tuberculosis, 2023)
Nearly two decades have passed since the first report on autophagy acting as a cell-autonomous defense against Mycobacterium tuberculosis. This helped usher a new area of research within the field of host-pathogen interactions and led to the recognition of autophagy as an immunological mechanism. Interest grew in the fundamental mechanisms of antimicrobial autophagy and in the prophylactic and therapeutic potential for tuberculosis. However, puzzling in vivo data have begun to emerge in murine models of M. tuberculosis infection. The control of infection in mice affirmed the effects of certain autophagy genes, specifically ATG5, but not of other ATGs. Recent studies with a more complete inactivation of ATG genes now show that multiple ATG genes are indeed necessary for protection against M. tuberculosis. These particular ATG genes are involved in the process of membrane atg8ylation. Atg8ylation in mammalian cells is a broad response to membrane stress, damage and remodeling of which canonical autophagy is one of the multiple downstream outputs. The current developments clarify the controversies and open new avenues for both fundamental and translational studies.